Subthalamic nucleus stimulation improves Parkinsonian gait via brainstem locomotor centers - Weiss, Peter H.; Herzog, Jan; Pötter-Nerger, Monika; Falk, Daniela; Herzog, Hans; Deuschl, Günther; Volkmann, Jens; Fink, Gereon R. (Movement disorders, 2015)
Background Subthalamic deep brain stimulation (STN‐DBS) can ameliorate gait disturbances in Parkinson's disease (PD). Using motor imagery and positron emission tomography (PET), we investigated how STN‐DBS interacts with supraspinal locomotor centers in PD. Methods Ten PD patients with bilateral STN‐DBS actually walked or stood still under STN‐DBS ON or OFF conditions. Directly thereafter, subjects imagined walking or standing while changes in regional cerebral blood flow were measured by PET. Results Independent of STN‐DBS, imagined walking distance correlated with imagery duration. Compared with STN‐DBS OFF, STN‐DBS ON improved actual gait and increased imagined walking distance. Imagery of gait (vs. stance) induced activity in the supplementary motor area and the right superior parietal lobule for both STN‐DBS conditions. The improvement of imagined gait during STN‐DBS ON led to activity changes in the pedunculopontine nucleus/mesencephalic locomotor region (PPN/MLR). Conclusions Data suggest that STN‐DBS improves Parkinsonian gait by modulating PPN/MLR activity. © 2015 International Parkinson and Movement Disorder Society